2021
DOI: 10.3389/fmicb.2021.621069
|View full text |Cite
|
Sign up to set email alerts
|

Zooming Into the Microbiota of Home-Made and Industrial Kefir Produced in Greece Using Classical Microbiological and Amplicon-Based Metagenomics Analyses

Abstract: Kefir is a high nutritional fermented dairy beverage associated with a wide range of health benefits. It constitutes a unique symbiotic association, comprising mainly lactic acid bacteria, yeasts, and occasionally acetic acid bacteria, which is strongly influenced by the geographical origin of the grains, the type of milk used, and the manufacture technology applied. Until recently, kefir microbiota has been almost exclusively studied by culture-dependent techniques. However, high-throughput sequencing, alongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 67 publications
(136 reference statements)
5
36
3
Order By: Relevance
“…Similarly, in a study conducted by Kazou et al . (2021), the microbiota of homemade and industrial kefir beverages was investigated. While the researchers detected Firmicutes as the dominant phylum in all samples, Proteobacteria were the mainly identified phylum in homemade kefir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study conducted by Kazou et al . (2021), the microbiota of homemade and industrial kefir beverages was investigated. While the researchers detected Firmicutes as the dominant phylum in all samples, Proteobacteria were the mainly identified phylum in homemade kefir.…”
Section: Discussionmentioning
confidence: 99%
“…Kazou et al . (2021) reported that, while Lactobacillus and Lactococcus were dominant in almost all grains and homemade kefir beverages, Streptococcus , Lactobacillus and Lactococcus were found to be dominant in industrial kefir beverages. The researchers also reported that due to the new taxonomy of lactic acid bacteria made by Zheng et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the microbiota of kefir grains and beverages produced in Greece were examined using a holistic approach combining classical microbiological, molecular and ampliconbased metagenomics analyses [68]. Although L. kefiranofaciens was not isolated using the growth media MRS and Rogosa, the amplification of the V1-V3 hypervariable region of the 16S rRNA gene revealed its occurrence in both kefir grains and beverages (unpublished data).…”
Section: Origin Detection Number Of Isolates Referencementioning
confidence: 99%
“…Lactic acid bacteria (LAB) are food‐fermentation agents involved in the manufacturing of yogurt, cheese, cultured butter, sour cream, sausages, cucumber pickles, olives, sauerkraut, and cocoa, among many other foods (Ho et al., 2018; Kazou et al., 2021; Mannaa et al., 2019; Nguyen et al., 2015; Todorov et al., 2017; Touret et al., 2018). However, some LAB species may spoil beer, wine, and processed meats (Laranjo et al., 2017; Ray & Joshi, 2015;).…”
Section: Introductionmentioning
confidence: 99%